Recovering the anthropological thing... a need of education (2014)
The paper has the aim of identifying the type of subject built both in the classroom and in the school context mediated by the reality that sets new educational challenges. Since the research problem was a qualitative one, it was carried out a sociolinguistics research exercise focused on the faceto-face interaction patterns in significant contexts or environments and in the cultural products. As a result, it is possible to state that the restrictive view of the educational process implies to foster, in the international and national academic community, a systematic consideration on the kind of subjectivity or professional identity promoted in the current educational processes. Then, it is concluded that it underlies the human construction that individuals live in their socio-historical dimension -since they have multiple meanings of their own reality-, which, in turn, looks for the construction of human condition as an opposition to the relationship between the theoretical and practical world.